The Knowledge Issues Enhanced the Teaching of Music Technology - Chiangthong, Nut; Nakpee, Nattanit (Journal of Roi Kaensarn Academi, 2024)
Teachers are underusing music technology in the classroom due to its many issues: Technology, pedagogy, and content knowledge are combined in the TPACK to improve teaching and learning. The purpose of this article is to study knowledge issues for enhancing the teaching of music technology. Music technology includes creation, wave data manipulation, and reproduction. Subject matter, teaching methods, and technology skills are essential for educational success. TPACK helps teachers learn and practice technology integration. It can impact teacher training and professional growth. Music production involves various tools, software, and hybrid teaching, promoting student-centered, patient-oriented learning. Creating music technology classes for instructors with limited expertise is crucial for online and offline learning. Data extraction, music recommendation, analysis, and music therapy are made easier with music software. Music technology offers new ways to enjoy and make music. Due to rapid change, the curriculum cannot keep up with instruction. Teacher methods include integrating disciplines and teaching methods, ICT, service learning, experiential learning, and cooperative learning. Successful music technology teaching requires proper technology use, computer skills, and a dedication to learning.